Evolution of noise pollution in the Botanical Garden of Curitiba, Brazil: A case study - Zaninin, P.H. T.; Szeremetta, B.; Diniz, F. B. (Archives of Acoustics, 2003)
A study has been conducted in the Botanical Garden of the city of Curitiba, Brazil, regarding to noise pollution found in this park and generated by the nearly streets. In order to do so, measurements of noise levels have been carried out in 21 points spread troughout the park, and some local visitors were interviewed. It has been found out that 47.6% out of the measurement sites has presented noise levels that have excended 65 dB(A), which is considered as the maximum noise level one can be exposed to according to the Preventive Medicine, and 95% out of the measerement points have showed levels over the local legislation, the law number 8583 from 1995, which states the noise limits allowed for the several urban zones of the city.